2009
DOI: 10.1038/jp.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic surfactants: where are we? Evidence from randomized, controlled clinical trials

Abstract: The benefits of exogenous synthetic or animal-derived surfactants for prevention or treatment of respiratory distress syndrome (RDS) are well established. Data from head-to-head trials comparing animal-derived surfactants primarily with the synthetic surfactant colfosceril suggest that the major clinical advantages afforded by the presence of surfactant protein (SP)-B and SP-C in animal-derived preparations relate to faster onset of action, a reduction in the incidence of RDS when used prophylactically, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…In the history of artificial surfactant development, early commercial synthetic surfactants included Exosurf® (GlaxoSmithKline, Brentford, UK) and Surfaxin® (Discovery Laboratories, Warrington, PA, USA). Exosurf® contains DPPC only without SP, while Surfaxin® has the synthetic peptide KL4 as an analogue of human SP-B 12. However, animal derived (bovine and porcine) natural SP has been found to be clinically superior to synthetic surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…In the history of artificial surfactant development, early commercial synthetic surfactants included Exosurf® (GlaxoSmithKline, Brentford, UK) and Surfaxin® (Discovery Laboratories, Warrington, PA, USA). Exosurf® contains DPPC only without SP, while Surfaxin® has the synthetic peptide KL4 as an analogue of human SP-B 12. However, animal derived (bovine and porcine) natural SP has been found to be clinically superior to synthetic surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Also, these surfactants contain foreign proteins that may be potentially immunogenic and infectious. 6 Synthetic surfactants, which are free of animal proteins, may have advantages over animal-derived surfactants due to their lack of immune reactions, proinflammatory mediators causing bronchopulmonary dysplasia (BPD), and animal-borne infectious agents. 6 They are also reproducible and have fewer production limitations than animal-derived surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown that its therapeutic effect was inferior to that of natural surfactant. The rise of protein-containing synthetic surfactant, such as lucinactant (Surfaxin ® ), has offered scientists a new avenue to further expand upon our advancement in surfactant as its action has been hypothesised to be as effective as, or even better than, natural surfactant [15,16]. The purpose of this review is to identify the key components of surfactant analogues, discuss the trials comparing surfactant types, analyse the methods of surfactant administration, and highlight recent developments.…”
Section: Introductionmentioning
confidence: 99%